2013
DOI: 10.1002/adfm.201302157
|View full text |Cite
|
Sign up to set email alerts
|

Performance Optimization of Vertical Nanowire‐based Piezoelectric Nanogenerators

Abstract: The integrated nanogenerator (NG) based on vertical nanowire (NW) arrays is one of the dominant designs developed to harvest mechanical energy using piezoelectric nanostructures. Finite element method (FEM) simulations of such a NG are developed using ZnO NWs in compression mode to evaluate its performances in term of piezoelectric potential generated, capacitance, induced mechanical energy, output electrical energy, and effi ciency. This evaluation is essential to correctly understand NG operation. Three main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
145
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 48 publications
6
145
0
Order By: Relevance
“…There remain many such contradictions between experimental results and the present theoretical understanding of ZnO NW-based devices when realistic doping levels are considered. Chief among them are (1) decent and length-dependent performance of ZnO NWs, [18] while anticipations based on analytical and computational study showed that the output of NWs under compression were reduced to a few millivolts and presenting length-independent performance due to the screening effect; [19,20] (2) enhanced piezoelectric coefficients, [21] which were measured for ZnO NWs with diameter beyond the size effects anticipated by ab initio method; [22] and (3) dissymmetric piezoelectric response of bent nanogenerators (NGs) under tensile and compressive strain. [23] Relatively high potentials (>0.2 V) can be repeatedly obtained from NGs integrating long and large ZnO NWs [24][25][26][27] with presumably nonintentional doping.…”
mentioning
confidence: 99%
“…There remain many such contradictions between experimental results and the present theoretical understanding of ZnO NW-based devices when realistic doping levels are considered. Chief among them are (1) decent and length-dependent performance of ZnO NWs, [18] while anticipations based on analytical and computational study showed that the output of NWs under compression were reduced to a few millivolts and presenting length-independent performance due to the screening effect; [19,20] (2) enhanced piezoelectric coefficients, [21] which were measured for ZnO NWs with diameter beyond the size effects anticipated by ab initio method; [22] and (3) dissymmetric piezoelectric response of bent nanogenerators (NGs) under tensile and compressive strain. [23] Relatively high potentials (>0.2 V) can be repeatedly obtained from NGs integrating long and large ZnO NWs [24][25][26][27] with presumably nonintentional doping.…”
mentioning
confidence: 99%
“…The capacitance increases along with the increase of the length of the PZT nanowire from 2.0 mm to 4.0 mm. As the length of PZT nanowire increases, the PZT proportion in the composite increases, which results in the increase of the dielectric constant of the composite, and further leads to a higher capacitance of the device under the fixed thickness [21].…”
Section: Resultsmentioning
confidence: 99%
“…(1). In addition, decreasing the distance between nanowire tip and the top electrode also contributes to the increase of the output voltage of the device because of the decrease of the electric potential transmission which is induced by the 3D dielectric losses [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation is very different for the device working in compression mode, previous work has shown that VING can sustain as high as 1 MPa compressive pressure [8].…”
Section: B Discuss On the Structure Strengthmentioning
confidence: 99%